Effect of drip irrigation and bioregulators on yield, economics and water use of fenugreek (Trigonella foenum-graecum) - M P Sahu, N C Sharma, K Balai, S R Bhunia, I M Verma, (Journal of Spices and Aromatic Crops, 2015)
The field experiment was conducted during winter seasons of 2009–10 and 2010–11 to assess the effect of drip irrigation levels and bioregulators (thiourea and Thioglycollic acid) on fenugreek. Increasing levels of drip irrigation from 0.6 to 1.0 ETc enhanced yield attributes viz., branches plant-1, pods plant-1, pod length, seeds pod-1 and test weight. Increased yield attributes with 1.0 ETc thus, enhanced seed yield (15.53 q ha-1) and stover yield (31.54 q ha-1). However highest B:C ratio (2.11) was recorded with 0.8 ETc irrigation level and highest water use efficiency of 4.83 kg ha-1 mm with 0.6 ETc. Recommended surface irrigation treatment recorded 13.02 q ha-1 seed yield with using 540 mm of water. Whereas, fenugreek under drip irrigation at 0.6, 0.8 and 1.0 ETc used 278.16, 370.88 and 463.60 mm of water, respectively. Seed treatment of fenugreek before sowing with bio-regulator thiourea (500 ppm) for 4 h recorded higher yield attributes viz., pods plant-1, pod length and test weight, as well as, seed yield of 14.85 q ha-1 against 14.36 q ha-1 where no seed treatment was done. Thus, in turn fetched higher water use efficiency (4.00 kg ha-1 mm) and B:C ratio (2.08). Further, foliar spray with 200 ppm thioglycollic acid at vegetative and seed formation stages recorded highest seed yield of 15.01 q ha-1 over 100 ppm thioglycollic acid spray (14.59 q ha-1) or no spray treatment (14.21 q ha-1). Increased yield thus enhanced water use efficiency (3.93-4.05 kg ha-1 mm) and B:C ratio (2.06-2.11) in thioglycollic acid treated crop.